Implementation of Good Governance Principles in the Monitoring and Evaluation of Public Service Delivery Performance (PEKPPP) in the Organizational Section of the Surabaya City Regional Secretariat - Maisarah Nabila; Vidya Imanuari Pertiwi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The government implements the Monitoring and Evaluation of Public Service Delivery Performance (PEKPPP) based on the principles of good governance to improve service quality. This study aims to analyze the implementation of good governance principles in the execution of PEKPPP at the Organizational Division of the Regional Secretariat of Surabaya City. The research employs a descriptive qualitative method, with data collected through observation and in-depth interviews with key informants selected purposively. The focus of the study includes the principles of equity, participation, accountability, transparency, efficiency, and accessibility. The findings indicate that the implementation of PEKPPP has been conducted in accordance with established guidelines and has substantively applied the principles of good governance, thereby contributing to the improvement of public service quality in Surabaya City.